Effects of time-of-day training preference on resistance-exercise performance - Blazer, H. J.; Jordan, C. L.; Pederson, J. A.; Rogers, R. R.; Williams, T. D.; Marshall, M. R.; Ballmann, C. G. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The purpose of this study was to investigate how time-of-day training preference influences resistance-exercise performance. Methods: Resistance trained males (n = 12) were recruited for this study. In a crossover, counterbalanced design, participants completed two separate bench-press exercise trials at different times of day: (a) morning (AM; 8:00 hr) and (b) evening (PM; 16:00 hr). Participants answered a questionnaire on time-of-day training preference and completed a preferred (PREF) and nonpreferred (NON-PREF) time-of-day trial. For each trial, motivation was measured using a visual analog scale prior to exercise. Participants completed 2 sets × 2 repetitions at 75% 1-RM with maximum explosiveness separated by 5 min of rest. Mean barbell velocity was measured using a linear position transducer. Participants then completed 1 set × repetitions to failure (RTF) at 75% 1-RM. Rate of perceived exertion (RPE) was measured immediately following exercise. Results: Regardless of preference, velocity (p = .025; effect size (ES) = 0.43) was higher during the PM versus AM trial. However, there were no significant differences in velocity (p = .368; ES = 0.37) between PREF and NON-PREF time of day. There were no significant differences for repetitions between PREF and NON-PREF times (p = .902; ES = 0.03). Motivation was higher in the PREF time versus NON-PREF (p = .015; ES = 0.68). Furthermore, RPE was significantly lower during the PREF time of day (p = .048; 0.55). Conclusions: Despite higher barbell velocity collectively at PM times, time-of-training preference did not largely influence resistance-exercise performance, while motivation is higher and RPE is lower during preferred times.